2009
DOI: 10.1007/s00011-009-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma calprotectin in chronically dialyzed end-stage renal disease patients

Abstract: Significantly elevated levels of plasma calprotectin in ESRD patients occur without an acute infectious cause and are not affected by the presence of diabetes. By analogy to plasma beta-2 microglobulin, a close relation of plasma calprotectin to HD vintage was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In addition, calprotectin was more strongly and independently associated with CV outcome and mortality than CRP. Our results, in accordance with previous reports (17,19,20,24), suggest that the regulation of calprotectin and CRP respond to different mechanisms and that calprotectin may be a more sensitive marker of the chronic inflammatory state than CRP. In our 5/6 Nx mouse model, increased plasma calprotectin was strongly correlated to renal function decline and monocyte count.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, calprotectin was more strongly and independently associated with CV outcome and mortality than CRP. Our results, in accordance with previous reports (17,19,20,24), suggest that the regulation of calprotectin and CRP respond to different mechanisms and that calprotectin may be a more sensitive marker of the chronic inflammatory state than CRP. In our 5/6 Nx mouse model, increased plasma calprotectin was strongly correlated to renal function decline and monocyte count.…”
Section: Discussionsupporting
confidence: 93%
“…Calprotectin is a marker of disease activity in many autoimmune and inflammatory diseases, including rheumatoid arthritis, inflammatory bowel disease, systemic lupus erythematous, or, more recently, COVID-19 (14)(15)(16). Some reports have shown that circulating calprotectin was increased in dialysis patients compared with healthy individuals (17,18) and that serum calprotectin was associated with overall mortality in hemodialysis patients with elevated serum phosphorus or patients on peritoneal dialysis (19,20). In addition, increased circulating calprotectin has been associated with a higher incidence of CV events in patients without CKD, including coronary events, peripheral arterial disease, and acute ischemic stroke (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of S100A8/A9 predicted risk of future myocardial infarction, stroke or death in post-menopausal healthy women [ 25 ]. Elevated S100A8 levels have also been found in other inflammatory disorders which are associated with abnormalities of vascular and cardiac function, particularly diastolic dysfunction, such as diabetes [ 46 48 ], end-stage renal disease [ 49 , 50 ], and inflammatory bowel disease [ 51 , 52 ]. This is the first association of S100A8 with HFpEF, yet its role in the disease process still needs be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to measure calprotectin levels in patients with ESKD have been reported by others with conflicting results. Malickova et al 27 found calprotectin levels elevated in patients with ESKD predialysis and unchanged after dialysis; intradialytic levels were not obtained. The focus of their study was not on neutrophil activation per se and the multiple parameters we assessed were not measured.…”
Section: Discussionmentioning
confidence: 98%